iPads in the foreign language classroom:a learner’s perspective - Gabarre, Cécile; Gabarre, Serge; Rosseni Din,; Parilah Mohd Shah,; Aidah Abdul Karim, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
This research paper presents the findings from the pilot study of a project exploring the potential of tablet computers in the foreign language classroom in a Malaysian public university. This article focuses on the technical amazements and challenges as experienced by a learner discovering her iPad 2 over four weeks. In-depth knowledge about the device’s user-friendliness and language learning potential was gathered through a narrative qualitative approach using classroom observations, field notes and interviews. The objectives were to unveil the learner’s perceptions toward the device as a novice user and to discover her strategies when handling the device for language learning. This study describes the learner’s intentions for adopting the iPad as a learning tool and how she overcame technological obstacles. It provides educators with hints on the learner’s tools and strategies for learning languages with the iPad as well as insights and recommendations to educators willing to venture into teaching languages with tablet computers.